Perancangan Sistem Informasi Penyewaan Kontrakan Berbasis Website untuk Mendukung Digitalisasi Menajemen Pengelolaan - EE Lailatul Putri; Zahra Nasywa Zain; Ath Thaariq; Eka Sofiati (Universitas 17 Agustus 1945 Jakarta, 2025)
The rapid development of information technology has encouraged digitalization in various sectors, including property rental management such as boarding houses. The manual management process often leads to several issues, such as disorganized tenant data, delays in monitoring payments, and errors in calculating late fees. This study aims to design and develop a web-based rental information system that automates tenant data management, payment recording, and real-time financial reporting. The research method used is the Agile Development Method, which includes planning, design, development, testing, and implementation stages. The system was developed using the PHP programming language and a MySQL database, and it can be operated both locally and online. The implementation results show that the system can facilitate tenant data management, automatically calculate late fees, and generate financial reports effectively and efficiently. Based on the testing results, all main features functioned properly according to user requirements. With this system, rental management becomes more structured, transparent, and easily accessible for both landlords and tenants in real-time.